STEM-21. REPURPOSING CLEMASTINE TO SUPPRESS GLIOBLASTOMA STEM CELLS. (14th November 2022) - Sun, Michael; Yang, Rui; Liu, Heng; Wang, Wenzhe; Song, Xiao; Hu, Bo; Reynolds, Nathan; Roso, Kristen; Chen, Lee; Greer, Paula; Cheng, Shi-Yuan; Ashley, David; et al.
Abstract: Glioblastoma stem cells (GSCs), also known as brain tumor initiating cells (BTICs), drive tumor progression, heterogeneity, and resistance to treatments, posing formidable challenges to advancing effective treatments against glioblastoma (GBM). We postulated that inducing BTIC differentiation can serve as a solution to diminishing their stem-like features. Here, we report that clemastine, an over-the-counter oral medication for allergy relief, attenuates stemness and proliferation of BTICs. These effects of clemastine were accompanied by altered transcriptional programs suggestive of a shift from maintaining stem cell identity to differentiation, resonating with the ability of clemastine to promote oligodendrocyte precursor cell (OPC) differentiation to mature oligodendrocytes. Genetic perturbation and small-molecule inhibition of putative pharmacological targets of clemastine revealed that Emopamil-binding protein (EBP), an enzyme in the sterol biosynthesis pathway, played a pivotal role in mediating the differentiating and anti-tumor effects of clemastine. Notably, loss-of-function assays showed that EBP expression was indispensable for BTIC propagation. In contrast, overexpression of EBP stimulated BTIC proliferation, thus uncovering a previously unknown role of sterol metabolism in BTIC maintenance. Finally, we demonstrated that a mouse neural stem cell-derived glioma model was similarly susceptible to clemastine treatment. Taken together, our study identifies pathways essential for the perpetuation of stemness in GBM, and implicates a non-oncology drug with a well-established safety profile that can be repurposed to mitigate the stem-like properties of GBM.